Sulfated tin oxide with macro- and mesopores controlled using an integrated sol-gel and surfactant template route - Alves-Rosa, Marinalva A. [UNESP]; Vasconcellos, Jonatas Z. [UNESP]; Vieira, Luiz H.; Santilli, Celso V. [UNESP]; Pulcinelli, Sandra H. [UNESP] (My University, 2019)
Sulfated tin oxide was synthesized by a sol-gel process and pores were formed in the ceramic powders using Pluronic F-127 as a soft template. Sulfate ions linked to the tin oxide promoted the formation of acid sites on the particle surfaces. After calcination, the sulfate ions remained on the oxide particles as uni- and bidentate complexes, so changes in the tin atom coordination numbers at the second shells could be observed by X-ray absorption spectroscopy. The tin oxides showed a cassiterite nanocrystalline structure consisting of aggregates of spherical particles, with crystallite size of around 8 nm, radius of gyration ∼3.7 nm, and mean particle size between 7 and 10 nm, according to X-ray diffraction and small angle X-ray scattering measurements, together with the use of transmission electron microscopy images. The use of Pluronic F-127 as a template for the pores resulted in the formation of meso- and macropores sized around 7.5 nm and 60 μm, respectively, surface area of 128 m2 g−1 and porosities of 71%, after calcination at 500 ºC. The porous sulfated tin oxide was used to catalyze the isopropanol dehydration reaction, with production of propene. The catalytic activity and the temperature-programmed desorption of ammonia confirmed the presence of acid sites on the surface, suggesting that this material could be employed as a heterogeneous catalyst in acid-catalyzed reactions.
Keywords: Acid site; Mesopore; Sulfate; Surfactant; Tin oxide